1999
DOI: 10.1002/(sici)1097-0274(199903)35:3<257::aid-ajim5>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in semen quality associated with decreasing occupational lead exposure

Abstract: Background Cross-sectional studies have suggested that occupational lead exposure may adversely affect sperm quality. Methods Sperm quality changes were prospectively assessed in 19 men employed at a car battery plant where efforts were made to decrease the exposure level. The participants delivered monthly samples of semen and venous blood during their employment at the factory. The factory then closed, and additional samples were obtained from 16 of the men.Results Average blood-lead concentrations decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
(35 reference statements)
2
11
0
1
Order By: Relevance
“…20 lg dl À1 (n = 11), while no significant difference was reported as regards spermatic count and abnormal forms when compared with the group PbB 20 lg dl À1 . Viskum et al (1999) reported that occupational lead exposure at acceptable levels has a small adverse effect on sperm quality, especially sperm motility. Other reports suggested that moderate exposures to Pb (<40 lg dl À1 ) can significantly reduce human semen quality without conclusive evidence of impairment of male reproductive endocrine function (Apostoli et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…20 lg dl À1 (n = 11), while no significant difference was reported as regards spermatic count and abnormal forms when compared with the group PbB 20 lg dl À1 . Viskum et al (1999) reported that occupational lead exposure at acceptable levels has a small adverse effect on sperm quality, especially sperm motility. Other reports suggested that moderate exposures to Pb (<40 lg dl À1 ) can significantly reduce human semen quality without conclusive evidence of impairment of male reproductive endocrine function (Apostoli et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The observed Pb-related effects on semen quality have also been indicated, to a certain extent, in the studies of other authors. These effects include a decrease in semen volume (17,21,26), a decrease in sperm density and sperm count (11,13,14,16,17,20,21), a decrease in sperm motility (15,16,20,21,28) and the quality of motility (17,28), an increase in abnormal sperm morphology (16,17,20,21,26) [particularly at the head of the sperm (17,21,26)], and impairment of the prostate secretory function as indicated by decreased SfZn (26). In most of these studies, significant alterations of reproductive parameters were observed at relatively higher BPb levels (> 400 pg/L), and only on a group basis (or in a few individuals); therefore, insufficient evidence was presented for establishing relevant dose-response relationships.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, relatively few data are available regarding the possible reproductive effects of Pb and/or Cd in men, and generally conflicting results have been reported in reviews on the subject (9,10). Nevertheless, the results of several studies suggest that relatively high occupational exposure to Pb, as indicated by blood Pb (BPb) levels, can reduce human semen quality (decreased number, motility, and altered morphology of sperm), whereas reproductive endocrine function is either not affected or is only marginally affected (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Some data suggest that the reproductive effects of Pb in men are reversible, that is, a trend toward normalization of reproductive parameters was found in subjects treated with a Pb-chelating agent (16,1/), or after cessation of occupational Pb exposure (28).…”
mentioning
confidence: 99%
“…Similarly, the occupational exposure to heavy metal slightly reduces sperm production in men (Viskum et al, 1999). However, this decrease seems to be transient and partially reversible (Viskum et al, 1999). Similarly, De Rosa et al found that all sperm parameters, except sperm count, were deranged in subjects continuously exposed to environmental pollutants (De Rosa et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Watanabe et al demonstrated that diesel engine exhaust stimulated hormonal secretion, depressed gonadotropin releasing hormone (GnRH) and inhibited spermatogenesis in the rat model (Watanabe and Oonuki, 1999). Similarly, the occupational exposure to heavy metal slightly reduces sperm production in men (Viskum et al, 1999). However, this decrease seems to be transient and partially reversible (Viskum et al, 1999).…”
Section: Introductionmentioning
confidence: 99%